Theoretical Study of The Ratio A/As Effect on Saturable Absorber Performance of Passive Q-switched Tm+3 Doped Fiber Laser System - Tahani M . Hussein; Abdul - Kareem Mahdi Salih; M. Benhaliliba (University of Thi-Qar Journal of Science, 2024)
The effect of the ratio of active media effective area to the saturable absorber effective area (A/As) on saturable absorber performance has been studied numerically for passive Q-switching fiber laser system doped with Tm+3 as an active medium and Cr+4:YAG crystal as a saturable absorber. Software program using Rang- Kutta- Fehalberge numerical method prepared in the study to carry out the simulation. The simulation shows that the increasing A/As value results in the generation of passive Q-witched pulses in shorter times, allowing optical bleaching of the saturable absorber material and convergence between ground absorption activity and excited levels occurs earlier in time.